"Moving the Rubble": Reflection, Conscientization, and Transformative Learning With Men Incarcerated for Organized Crime in Mexico. (October 2022) - Strickland, Rebecca Danielle
While many scholars have examined transformative learning in different prison education programs, the field has only recently reached Latin America. This article presents a participatory action research project which has been operating in a prison for men accused of organized crime in Jalisco, Mexico, since 2018. The analysis is based on testimonies related to personal and collective transformation in a context of multifaceted oppression. It also explores the blurry lines between reflection, conscientization, and transformation, inviting us to consider how transformative education relates to social stigma and freedom.